PENGARUH PERLAKUAN SODIUM TRIPOLYPHOSPHATE (STPP) PADA PATI SAGU TERMODIFIKASI TERHADAP KETEBALAN, TRANSPARANSI DAN LAJU PERPINDAHAN UAP AIR EDIBLE FILM - Maharani, Yulia; Hamzah, Faizah; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The use of native starch in production the edible film have weakness characteristic is vulnerable. Therefore, modified of the starch was necessary improved the functional properties of native starch. The purpose of this research was to determined the best of modified starch with concentrations of sodium tripolyphosphate (STPP) in making modified starch as raw material for edible film. This research used Completely Randomized Design (CRD) with four treatments and four replication followed by DNMRT test at 5%. The treatments in this research was S1 (STPP 0%), S2 (STPP 0.5%), S3 (STPP 1,0%) and S4 (STPP 1.5%). The resultsshowed that the use of modified starch in a different concentration of sodium tripolyphosphate (STPP) with has significant affected on the transparency, water vapor transmission rate, tensile strength and elongationhowever not significant affected on the thickness. The best treatment edible film of modified starch in a different concentration of sodium tripolyphosphate (STPP) in this research was S4 (STPP 1.5%) with thickness 0.0822 mm, transparency of the value 3.3110, water vapor transmission rate 22.7418 g /m2/h, tensile strength 1.7706 MPa, and elongation 19.3269%. Keywords: modified starch, cross-linking, sodium tripolyphosphate, edible film.